Assessment of geomorphological and hydrological variations in Bhagirathi River Drainage sub-basin with the help of morphometric studies - Naval Kishore Tewari; Anil Kumar Misra; Anshumali Sharma (Journal of Taibah University for Science, 2019)
Interpretation of geomorphic features and drainage characteristics of Bhagirathi River sub-basin was carried out with the help of morphometric analysis. Various, areal, linear and relief parameters were calculated to assess drainage basin characteristics quantitatively, determine infiltration and surface runoff behavior control of drainage. The drainage network was analyzed using IRS-PAN satellite data and Survey of India toposheets. Findings show that the Bhagirathi sub-basin from Gaumukh to Chirbas exhibits dendritic to sub-dendritic drainage patterns and is characterized by third-order streams up to Chirbas. Stream segments development in the basin is controlled by local relief and slope. The bifurcation ratio indicate disparity of bifurcation between the different stream orders owing to structural control  and circularity ratio indicates sub-elongated shape of basin. This study will be helpful for making soil erosion prevention strategies and its conservation and facilitate the understanding of water retention function in river basins.